MISTRANSLATED NEWS REPORT ON COPENHAGEN SHOOTING IN 2015 HUMAN ERROR OR INTENTIONAL ACT? - Panca Javandalasta; Cininta Aprina; Angkita Wasito Kirana (Department of Master of Linguistic, Universitas Airlangga, 2018)
The present study aims to analyze how translation in news reports can be seen unethical even though news report and translation are two aspects that should be guaranteed for its credibility, actuality, and precision. In analyzing this issue, a case of mistranslation in news reporting the Copenhagen shooting in 2015 that was published by detik.com was studied. To obtain the data, several news reports regarding the same issue that was published by several news portals around the globe in the same period of time were collected. Several reports from Indonesian news portal were also collected to see whether there was a similarity in presenting the content. The corpus-based analysis was also conducted to analyze the characters portrayed in the reports published by detik.com regarding the shooting. The result shows that only detik.com presents the mistranslated fact in the report, meanwhile the other Indonesian news sites report the contrary. The corpus-based analysis found that among the portrayed characters, Detik.com seemed to create an impression which leads the readers to think that there were two opposing sides; the suspect of shooting as the representative of the Muslim; and the cartoonist and the Ambassador which represent the non-Muslim. The mistranslated facts at detik.com seemed to please the Moslem side since, as a news site published in a country which majority citizens are Muslim, the readers of detik.com were also Moslem in the majority.